Dense Molecular Gas Around Protostars and in Galactic Nuclei 2005
DOI: 10.1007/1-4020-3831-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Maser Action in Methanol Transitions

Abstract: We report the detection with the ATCA of 6.7 GHz methanol emission towards OMC-1. The source has a size between 40 ′′ and 90 ′′ , is located to the south-east of Ori-KL and may coincide in position with the 25 GHz masers. The source may be an example of an interesting case recently predicted in theory where the transitions of traditionally different methanol maser classes show maser activity simultaneously. In addition, results of recent search for methanol masers from the 25 and 104.3 GHz transitions are repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Perhaps more importantly, modelling predicts that in some conditions the 6.6‐GHz class II transition can be weakly inverted, simultaneously with strong inversion in the 25‐GHz class I transitions. This situation may have recently been detected towards the archetypal class I maser source Orion KL (Voronkov et al 2005). Kurtz, Hofner & Álvarez (2004) found coincidence within 0.5 arcsec of class I and II methanol masers in one source, although there is a significant velocity difference between the two transitions suggesting that it may be a chance alignment along our line of sight.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Perhaps more importantly, modelling predicts that in some conditions the 6.6‐GHz class II transition can be weakly inverted, simultaneously with strong inversion in the 25‐GHz class I transitions. This situation may have recently been detected towards the archetypal class I maser source Orion KL (Voronkov et al 2005). Kurtz, Hofner & Álvarez (2004) found coincidence within 0.5 arcsec of class I and II methanol masers in one source, although there is a significant velocity difference between the two transitions suggesting that it may be a chance alignment along our line of sight.…”
Section: Introductionmentioning
confidence: 79%
“…The majority of the well‐studied class I methanol maser sources are ‘traditional’ class I sources with no (or weak) class II emission, Orion KL (Plambeck & Wright 1988; Johnston et al 1992), DR21 (Batrla & Menten 1988; Plambeck & Menten 1990) and Sgr B2 (Mehringer & Menten 1997). There are no strong class II methanol masers towards Orion KL, although weak masers, and possibly quasi‐thermal emission has been detected (Voronkov et al 2005). There is class II methanol maser emission towards DR21(OH), this likely to be from the same region as the OH maser emission (which is offset from the class I masers), but this has not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The maser was associated with a massive protostellar core that could host a nascent high-mass star. Recent observations by Voronkov et al (2004) have also revealed methanol emission at 6.7 GHz in the OMC-1 region near the 25-GHz maser site, i.e. a class I maser source.…”
Section: Follow-up Observationsmentioning
confidence: 93%